Settling Aftermath Regimes: Transitional Southern Albanian (Tosk) Orthodox Christians in the post-Ottoman World, 1822–1932 - Blumi, Isa (Archiv orientální, 2023)
During the "Age of Revolution," European empires reconfigured to become the modern states associated with the era. This symbiotic relationship between the historical center and the periphery increasingly acknowledged among scholars has its equivalent with respect to the Eastern Mediterranean. With these changes in European empires' metropole as a backdrop, this article explores heretofore ignored actions of Albanian Ottomans, adaptations, and even resistance that informed the evolution of diplomacy and international law after the Balkan Wars of 1912-1913. By monitoring the collective action of a particular group of Albanian Orthodox Christians who established themselves in diasporas in Egypt and North America, it may be possible to discover new contributions to the transformations impacting the larger Ottoman Empire and its Balkan/ Eastern Mediterranean territories.